Accidental Intraoperative Mandibular Fracture in a Third Molar Surgery: When Surgical Skills Are Mandatory in the Face of Empiricism - John Nadson Andrade Pinho; Lucas Alves da Mota Santana; Leandro Napier de Souza; Paulo Nand Kumar; Paulo Almeida Júnior; Liane Maciel de Almeida Souza (Hindawi Limited, 2023)
Iatrogenic mandible fractures are rare complications from third molar removal surgeries. While most documented cases stress risk factors inherent to the patient and tooth presentation in fractures' etiology, appreciation of the risk factors underlying the practitioner's skills is scarce. Here, we describe an intraoperative fracture in a healthy 26-year-old female resulting from an incompatible surgical technique during the right mandibular third molar removal. The patient showed facial swelling, pain, malocclusion, and significant mobility of the fractured segment. The surgical management involved an intraoral open reduction with the installation of titanium plates for the fixation of the bone segments. Thus, we highlight that acknowledging the extent of the operator's surgical skills should be part of comprehensive treatment planning, serving as a valuable measure to prevent iatrogenic mandible fractures besides avoiding a traumatic experience for the patient.